Perbandingan Chlorhexidine 0,5% dan Povidone Iodine 10% dalam Mencegah Kolonisasi Bakteri pada Kateter Epidural - Harianto, Widi Yuli; Mahmud; Widodo, Untung (Jurnal Komplikasi Anestesi, 2020)
Background: Infection in the epidural space is rare but if it occurs it is a serious complication of epidural catheter placement. Aromaa et al reported 8 cases of bacterial infection in the spinal or central nervous system (CNS) after 170,000 epidurals and 550.00 spinal anesthesia, with an overall frequency of 1.1 per 100,000 blocks. The purpose of this study was to compare chlorhexidine 0.5% with 10% povidone iodine in preventing bacterial colonization of epidural catheters in patients treated at the Central General Hospital (RSUP) Dr. Sardjito. Methods: The study design was a single-blind randomized controlled trial in 52 patients who had epidural anesthesia or a combination of general and epidural anesthesia at RSUP Dr. Sardjito Yogyakarta in JanuaryApril 2019. The research subjects were divided into two groups, namely clorhexidine 0.5% in 70% alcohol and povidone iodine 10%. Examination of the epidural catheter (3-4 cm) tip culture on the 3rd day after installation. The research data was tested using the Chi-Square test. Results: This study found positive bacterial cultures on chlorhexidine 0.5% and povidone iodine 10% each in 13% of 23 epidural catheters (p> 0.05). Risk factors for the incidence of spinal needle bacterial colonization which include age, sex, history of diabetes, autoimmune diseases, cytostatica therapy, HIV / AIDS infection, steroid use more than 2 weeks and type of surgery, antibiotic use and irritation events, and complications between the two groups there was no significant difference (p.0,05). Conclusion: The effectiveness of chlorhexidine 0.5% in 70% alcohol compared to povidone iodine 10% did not differ significantly in preventing bacterial colonization in epidural catheters, there was a growth of 13% (3/23) in the chlorhexidine 0.5% group in 70% alcohol and 13 % (3/23) in the povidone iodine 10% group